FAKTOR – FAKTOR YANG BERPENGARUH PADA KINERJA KEUANGAN PERUSAHAAN (STUDI KASUS PADA PT. PERKEBUNAN NUSANTARA XIV (PERSERO) UNIT LUWU I SULAWESI SELATAN - Misbahuddin Misbahuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aimed to analyze the factors that affect the company's financial performance. These factors proxy into net profit margin, assets turn over and return on investment. In this study researches analyze and process financial statement of PT Perkebunan Nusantara XIV Unit Luwu I from 2013 to 2017by calculating the calculation on each et profit margin, assets tuen over and return on investment. Based on research that has been conducted on PT Perkebunan Nusantara XIV Unit Luwu I.The results of this study indicate that financial performance with net profit margin, assets tuen over and return on investment still have fluctuated value even return on investment at value over industry standard is 15%.